Pengaruh Rekrutmen Terhadap Kinerja Karyawan Pada PT.X di Kota Semarang - Charity, Lintang Hening; Rahayu, Puspita Puji (Universitas Medan Area, 2024)
This research aims to see the effect of recruitment on employee performance at PT. X in Semarang City. The problem focused on is the performance carried out by employees at PT. X in Semarang City. Ti approaches this problem, a theoretical reference is needed according to Mangkunegara (2016) who interprets employee performance, as a result, a person’s work in terms of quality and quantity that has been achieved by employees Ijn carrying out their duties according to their assigned responsibilities. The type of research carried out in this research uses quantitative methods with simple linear regression analysis techniques. Data collection using a Likert scale. The sample used in this research was simple random sampling. The data collection method used a questionnaire belonging to Erny Dita Rosalina (2021). The sample taken in this study was 30 employees. The results of research using linear regression techniques show that there is a positive and significant influence between recruitment on employee performance with a known significance value of 0,165 0,05,. The results of this research conclude that the higher the recruitment process, the higher the employee performance will be.